(untitled) (ModaPalavra e-periódico, 2020)
This article examines the impact of the side effects of breast cancer treatment on women’s self-image. Qualitative and descriptive research was used, complemented with field research with three women with breast cancer as a sample. After analyzing the data, it was possible to verify that there are impacts on women’s self-image, especially when the side effects of the treatments begin to be felt.